(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the role of innovative technologies in the system of geography and other natural sciences and their effectiveness. Currently, the educational system requires an approach in New Ways, and the need to train pedagogical personnel can effectively use these methods is also emphasized. And in this article, national parks are focused on studying the geoecological aspects of zoning areas functionally. In this process, the methods of using the technology of geographic information systems are put into question. The more areas allocated in the structure of the National Park model, the more complex the composition and management process of zoning them. In addition, in national parks with a complex zoning system, the adaptation of local residents is also difficult. Because for the population, the organization of work activities in the Hol, which follows the established restrictions on the use of nature in each allocated zone, is a complex process.